Pandemi Covid 19: Bagaimana Kondisi Likuiditas Bank Syariah di Indonesia? - Kharis Fadlullah Hana; Muslikhatul Aini; Lorena Dara Putri Karsono (Al Maal: Journal of Islamic Economics and Banking, 2022)
The covid-19 pandemic has affected various sectors of life, not only offecting the healt sector, but also having an impact on the world economy and the banking sector. This study was conducted to analyze the liquidity condition of Islamic banking in the midst of the covid-19 pandemic. The research method used is qualitative research using descriptive analysis. The data collection method used is literature study, in written and digital form, such as journal articles, google books, and others. The results of the study show that the level of liquidity of islamic banking in Indonesia is in the quite adequate category, meaning that it is in a safe position even during the covid-19 pandemic.